1987
DOI: 10.1111/j.1439-0450.1987.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Lesions of Sweet Itch and the Distribution of Dermal Mast Cells in the Horse

Abstract: Summary Intradermal skin tests using insect allergens were carried out in different regions of two horses; a horse with sweet itch and a clinically normal horse. There was greater variation in the response at challenge sites on the horse with sweet itch than on the normal horse. Mast cell counts were performed on skin samples taken from a number of regions of seven horses. While these cells tended to be more numerous along the dorsal mid‐line no clear pattern emerged which could be associated with the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…This is in contrast to man, 39 dogs 36 and cats 40,41 where mast cells containing both tryptase and chymase are the major subtype in the skin. An earlier report described how mast cells tended to be more numerous along the dorsal midline, 42 but our findings were in agreement with the observations of Shearer 43 who found no significant differences in mast cell count in different body sites but significant differences between animals. We found the fetlock area had different mast cell counts but as this was not a biopsy site in any of the other disease groups it was not of significance in our study.…”
Section: Discussionsupporting
confidence: 93%
“…This is in contrast to man, 39 dogs 36 and cats 40,41 where mast cells containing both tryptase and chymase are the major subtype in the skin. An earlier report described how mast cells tended to be more numerous along the dorsal midline, 42 but our findings were in agreement with the observations of Shearer 43 who found no significant differences in mast cell count in different body sites but significant differences between animals. We found the fetlock area had different mast cell counts but as this was not a biopsy site in any of the other disease groups it was not of significance in our study.…”
Section: Discussionsupporting
confidence: 93%
“…While most of the IgE-mRNA+ cells were located in the deeper dermis, a high proportion of the IgE-protein+, metachromatically-stained cells and tryptase+ mast cells were found in the subepidermal layer of the dermis. Our results confirm, as had been shown by Morrow et al (1987), that equine mast cells are located mainly in the superficial layer of the dermis.…”
Section: Discussionsupporting
confidence: 92%
“…The entire surface of the epidermis was counted separately. As Morrow et al (1987) have demonstrated that mast cells are more numerous in the superficial layer of the dermis, a subepidermal layer was evaluated separately. This subepidermal layer was defined as the dermal part just under the epidermis (0.296 mm depth, corresponding to one side of the square reticule); 5 adjacent square reticules were counted in the subepidermal layer (0.296 mm depth x 1.48 mm length =0.438 mm 2 ), separately from the deeper part of the dermis.…”
Section: Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…was made 60 years ago in Australia by Riek (58,59); the presence of a reagenic antibody specific for Culicoides antigens was subsequently demonstrated in serum of affected horses (60). During the ensuing decades, several studies in diverse continents replicated these findings and hypersensitivity of horses to Culicoides bites became recognized as one of the commonest skin conditions to affect horses worldwide (48,52,(61)(62)(63)(64)(65). The role of Culicoides as the source of the allergen causing this condition was further strengthened by the observations that IBH does not occur in Iceland where Culicoides are absent, although other biting insects such as Simulium spp.…”
Section: Insect Bite Hypersensitivitymentioning
confidence: 91%